Feministična vstopanja v uprizoritvene umetnosti - Smerkolj Simoneti, Jaka (Amfiteater (Ljubljana), 2025)
The article examines the series of lecture-performances about the sexual pleasure of women, Sex Education II, directed by Tjaša Črnigoj, as an example of feminist theatre in Slovenia. It begins by exploring the intersections of feminist theories and performing arts. Each component in the series (Diagnosis, Consentire, Ability, Play, Fight) reflects on feminist approaches to performance practice, both in the production and the creative process, wherein the focus on documentary theatre plays a decisive role in the thematic and formal analyses of the performances. Sex Education II gradually transitions from addressing issues of women’s bodies to broader questions about the position of women in society and the influence of patriarchy on the most intimate aspects of their lives. Diverse strategies for approaching stage material and conveying it to the audience reveal the intersectionality of feminist theatre as realised in Sex Education II.
Keywords: documentary theatre; dokumentarno gledališče; feminist performance studies; feminist theatre; feministične študije scenskih umetnosti; feministično gledališče; Sex education II; Spolna vzgoja II; Tjaša Črnigoj